A preliminary investigation into the relationship between plant health and branch labelling technique at the Royal Botanic Garden Edinburgh - Bradley, Paul; Cubey, Robert (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2011)
Anecdotal evidence exists at the Royal Botanic Garden Edinburgh (RBGE) to suggest that branches bearing plant labels are more prone to die-back than those without labels. During 2010–2011 a preliminary study was undertaken in order to assess the accuracy of this hypothesis and to investigate the possible causes and viable alternatives. The study focused on whether there were patterns of damage with respect to label material and wire, plant species or the location of plantings. The study involved a survey of the Living Collection in the four RBGE Gardens, a web-based questionnaire sent out to Botanic Gardens Conservation International member gardens and analysis of branch material and labelling wire. This report provides the information obtained when the hypothesis was investigated and makes recommendations. An extended version, along with the data gathered, is available in the Library at RBGE (Bradley, 2011).